Emricasan (IDN‐6556) Lowers Portal Pressure in Patients With Compensated Cirrhosis and Severe Portal Hypertension. Issue 2 (26th November 2018) - Garcia‐Tsao, Guadalupe; Fuchs, Michael; Shiffman, Mitchell; Borg, Brian B.; Pyrsopoulos, Nikolaos; Shetty, Kirti; Gallegos‐Orozco, Juan F.; Reddy, K. Rajender; Feyssa, Eyob; Chan, Jean L.; Yamashita, Mason; Robinson, James M.; et al.
Abstract : Caspases play a central role in apoptosis, inflammation, and fibrosis. They produce hemodynamically active, proinflammatory microparticles that cause intrahepatic inflammation, vasoconstriction, and extrahepatic splanchnic vasodilation. Emricasan is a pan‐caspase inhibitor that lowers portal hypertension (PH) and improves survival in murine models of cirrhosis. This exploratory study assessed whether emricasan lowers PH in patients with compensated cirrhosis. This multicenter, open‐label study enrolled 23 subjects with compensated cirrhosis and PH (hepatic vein pressure gradient [HVPG] >5 mm Hg). Emricasan 25 mg twice daily was given for 28 days. HVPG measurements were standardized and performed before and after emricasan. A single expert read all HVPG tracings. Median age was 59 (range 49‐80); 70% were male. Cirrhosis etiologies were nonalcoholic steatohepatitis and hepatitis C virus. Subjects were Child class A (87%) with a median Model for End‐Stage Liver Disease score of 8 (range 6‐15). Twelve had severe PH (HVPG ≥12 mm Hg). Overall, there was no significant change in HVPG after emricasan (mean [standard deviation, SD] –1.1 [4.57] mm Hg). HVPG decreased significantly (mean [SD] –3.7[4.05] mm Hg; P = 0.003) in those with severe PH: 4/12 had a ≥20% decrease, 8/12 had a ≥10% decrease, and 2/12 HVPG decreased below 12 mm Hg. There were no significant changes in blood pressure or heart rate. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) decreased significantly in the entire group and in those with severe PH. Serum cleaved cytokeratin 18 and caspase‐3/7 decreased significantly. Emricasan was well tolerated. One subject discontinued for nonserious adverse events. Conclusion: Emricasan administered for 28 days decreased HVPG in patients with compensated cirrhosis and severe PH; an effect upon portal venous inflow is likely, and concomitant decreases in AST/ALT suggest an intrahepatic anti‐inflammatory effect.